Nutritional significance, value‐added applications, and consumer perceptions of food legumes: A review - Nicole S. Affrifah; Mark A. Uebersax; Samir Amin (Legume Science, 2023)
Abstract Legume crops are widely grown worldwide and a primary source of proteins across many least developed countries. These food crops are inherently produced in environmentally sustainable manner and are also an economical source of plant‐based proteins versus animal‐based proteins. The nutrient composition of legumes is very rich, that is, high content of protein, fiber, and bioactive compounds and relatively lower carbohydrates than cereal crops. Although food legumes are a staple in more than 70 countries mostly in Asian, African, and South American regions, the per capita consumption in the Western countries continues to be low in spite of legumes' demonstrated health benefits. However, emerging consumer trends and preferences toward heathy foods, animal protein alternatives, and environmental concerns can enhance the consumption of legume‐based foods. The functional attributes of legume ingredients (e.g., thickening, water‐holding index, gelation, emulsification, and foaming capacity) make legumes suitable for replacing proteins from other sources. The development and marketing of legume‐based ingredients for use in various value‐added food applications have been increasing. The value‐added use of pulse protein isolates and concentrates is expanding fast with substantial use as meat extenders/replacers and meat analogs, milk substitutes, and gluten‐free applications. To increase the utilization of legumes, including legume‐based foods, it is important to focus on research and development efforts that promote “easy‐to‐cook”/prepare foods for consumers, who often avoid legumes due to long cooking times. Addressing this aspect of convenience is particularly critical in developed countries due to the busy lifestyles of consumers and potentially increase legume consumption.